Ecosystems knowledge modeling and analysis method for information and communication - Szoniecky, Samuel (Digital tools and uses set ;, 2018)
To analyze complex situations we use everyday analogies that allow us to invest in an unknown domain knowledge we have acquired in a known field. After a history of the ecosystem concept and these derivatives (nature, ecology, environment) from antiquity to the present, the analysis method based on the modeling of socio-semantic ontologies is presented, followed by practical examples of this approach in the areas of software development, digital humanities, Big Data, and more generally in the area of complex analysis.